PENGUKURAN KINERJA TERHADAP PENGGUNAAN SISTEM INFORMASI PENERIMAAN MAHASISWA BARU DENGAN METODE TIME MOTION STUDY - Muhammad Taufiq; Taofik Muhammad; Alfadl Habibie (INFOTECH journal, 2022)
New Student Admissions (PMB) for a tertiary institution is an activity that is always carried out every year, therefore PMB activities are expected to make a significant contribution to the use of the information system for new student admissions in total, thereby having an impact on increasing work efficiency, effectiveness and productivity. in the form of satisfaction for PMB officers and prospective new students. The problem that often arises is that the performance of PMB officers in one unit of time is not well organized, regarding the volume of work, the time between one activity and the next (response time) and productive work time (productivity time), where the cause of the problem is the large amount of data. (information) that is lost or difficult to track includes less effective presentation of information, resulting in a lot of wasted performance and less productivity. For this reason, it is necessary to measure the performance of information needs for higher education management, especially in the new student admissions section, so that the performance of PMB officers can be formulated regarding the use of the New Student Admissions Information System which is right on target, effective and productive. Performance measurement of the use of the New Student Admissions Information System in this case uses the Time Motion Study method with a case study at the Muhammadiyah University of Tasikmalaya